THE ROLE OF WOMEN ENTREPRENEURSHIP IN THE HOUSEHOLD ECONOMY REVIEWED FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Nugroho, Mahfud; Erikawati, Civi (Universitas Muhammadiyah Surakarta, 2023)
Women entrepreneurs play an important role in helping stabilize the economy. Women's orientation to become an entrepreneur is influenced by goals, motives, women's identity and individual characteristics. The realization of women's empowerment and gender equality is one of the priority targets of the Sustainable Development Goals (SDGs). Female entrepreneurs are still considered physically and mentally weak, considered more emotional and less able to balance household work with their business activities. The aim of this research is to analyze the rights and obligations of women who work as businesspeople in terms of gender equality based on a sharia economic perspective. This research analyzes various library sources, both primary sources such as the Al-Quran and Al Hadith as well as library sources from contemporary Islamic figures. The research results show that Islam does not prohibit women from carrying out activities outside the home. Doing good deeds, both men and women who believe in Allah and His Messenger will be rewarded with happiness in this world and the hereafter. Women may carry out activities outside the home but do not abandon their obligations as a wife and mother.